Medical Narratives and Patient Analogs: The Ethical Implications of Electronic Patient Records - Kluge, E.-H. W. (Methods of Information in Medicine, 1999)
An electronic patient record consists of electronically stored data about a specific patient. It therefore constitutes a data-space. The data may be combined into a patient profile which is relative to a particular speciality as well as phenomenologically unique to the specific professional who constructs the profile. Further, a diagnosis may be interpreted as a path taken by a health care professional with a certain specialty through the data-space relative to the patient profile constructed by that professional. This way of looking at electronic patient records entails certain ethical implications about privacy and accessibility. However, it also permits the construction of artificial intelligence and competence algorithms for health care professionals relative to their specialties.
Keywords: Electronic Patient Record; Ethics; Data-space; Information; Diagnosis; Narrative